Study of the role of wall teichoic acids in the localization Staphylococcus aureus cell wall synthesis protein PBP4 - Henriques, Gabriela Fernandes (2016)
The cell wall of Staphylococcus aureus is a highly complex network mainly composed of highly cross-linked peptidoglycan (PG) and teichoic acids (TAs), both important for the maintenance of the integrity and viability of bacteria. The penicillin binding proteins (PBPs), which catalyse the final stage of PG biosynthesis, are targets of β-lactam antibiotics and have been a key focus of antibacterial research. S. aureus has four native PBPs, PBP1-4 carried by both methicillin-sensitive (MSSA) and –resistant (MRSA) strains. PBP4 is required for the synthesis of the highly cross-linked PG and, as shown in recent studies, is essential for the expression of β-lactam resistance in community-acquired strains (CA-MRSA). This protein has a septal localization that seems to be spatially and temporally regulated by an unknown intermediate of the wall teichoic acids (WTA) biosynthesis pathway. Therefore, if WTA synthesis is compromised, PBP4 becomes dispersed throughout the entire cell membrane. The aim of this project was to identify the WTA precursor responsible for the septal recruitment of PBP4. In order to do so, inducible mutants of tarB and tarL genes in the background of NCTCPBP4-YFP were constructed allowing for the study of PBP4 localization in the presence and absence of these specific tar genes.With this work we were able to show that the absence of TarB or TarL leads to the delocalization of PBP4, indicating that TarL or a protein/WTA precursor whose localization/synthesis is dependent on TarL is responsible for the recruitment of PBP4.